Livestock producers' knowledge, attitude, and behavior (KAB) regarding antimicrobial use in Ethiopia - Tufa, T.B.; Regassa, F.; Amenu, Kebede; Stegeman, J.A.; Hogeveen, H. (Frontiers Media, 2023)
Introduction: Inappropriate antimicrobial use (AMU) in livestock production is an important aspect of the global burden of antimicrobial resistance (AMR). In Ethiopia, a low-income country with a large and increasing livestock population, AMU in food animals is not properly regulated. Hence, farmers are fully free to use antimicrobials to their (perceived) benefit. Therefore, understanding farmers' mindsets is important to improve antimicrobial stewardship in the livestock sector.